أثر كتاب جامع الأمهات لابن الحاجب في خدمة المذهب المالكي وتطوره - زغدود, ياسين; ميهوبي, علي (جامعة الوادي - University of Eloued, 2022)
ملخص: قدم ابن الحاجب خدمة جليلة للفقه المالكي بتأليفه كتاب جامع الأمهات الذي يُعد عصارة جهده بعد أن نضج الفقه المالكي واستوى عنده، وقد أصبح كتاب ابن الحاجب أكثر الكتب الفقهية اعتمادا عند المالكية منذ تأليفه إلى ما بعد ظهور مختصر خليل، وعلى هذا الأساس فقد نال الكتاب مكانة مرموقة ومنزلة عالية عند أهل المذهب. فجاء هذا البحث ليكشف عن شخصية ابن الحاجب المتميزة ويبرز اسهاماتها في نصرة المذهب المالكي وخدمته له، وذلك من خلال كتابه القيم جامع الأمهات. كما توصل البحث إلى أن كتاب جامع الأمهات أسهم بشكل واضح وجلي في تكملة بناء صرح المذهب المالكي تأصيلا وتفريعا واجتهادا، وترك آثارا بارزة في خدمة المذهب. Abstract : Ibn al-Hajeb rendered a great service to the Maliki Fikh by authoring the book “Jami’ al-Ummat” which is considered the juice of his effort after the Maliki Fikh had matured and settled with him, Ibn al-Hajib's book has become the most trusted jurisprudential book for the Malikis since its authorship until the appearance of “Mukhtasar Khalil”, On this basis, the book won a prestigious position and a high position among the members of the sect. This research came to reveal the distinguished personality of Ibn al-Hajeb and highlight its contributions in supporting and serving the Maliki school of thought, through his valuable book “Jami’ al-Ummat”. The research also found that the book “Jami’ al-Ummat” contributed clearly and explicitly to the completion of the building of the Maliki school edifice by rooting, branching and ijtihad, and leaving prominent traces in the service of the doctrine.
Jami’ al-Ummat Ibn al-Hajeb in the service of The effect of the book the Maliki school of thought and its development
مقال
Keywords: ابن الحاجب؛ جامع الأمهات؛ أثر؛ خدمة؛ تطور؛ المذهب المالكي; Ibn al-Hajeb; Jami’ al-Ummat; Effect; Service; Evolution; The Maliki school of thought.